Serial verb constructions in Papuan Malay - Sawaki, Yusuf (LITERA, 2023)
Serial verb constructions are grammatical constructions that are still debatable by linguists from different schools of theories because of whether they are considered as simple or complex predicates in terms of their various structures found in world's languages. Creol languages such as Papuan Malay has serial verb constructions interested for further studies because there are lacks of similar studies done in the language. This research describes serial verb constructions in Papuan Malay. Its focus is to investigate syntactic and semantic structures of serial verb constructions. In the research, the descriptive linguistic method is used and its approach is the typological analysis where it focuses on analyzing particular linguistic features, i.e. serial verb constructions. The elicitation technique is used to collect data and it is also beneficial to supplement the syntagmatic analysis when the data is analysed in linear/horizontal order to easily look for the syntactic structure, argument structure, and argument sharing of serial verb constructions. The results show that serial verb constructions in Papuan Malay has two types, i.e. Dependent and Co-dependent serializations. Both types are categorized based on their argument structure and argument sharing properties, as well as their semantic expressions. Further, they are categorized as serial verb constructions by the definition of sequence of events within a monoclausality as the main feature of serial verb constructions in Papuan Malay. This paper gives a contribution to the theory of syntax and typology about the structural and semantic expressions of the serial verb constructions by reflecting the serial verb constructions in Papuan Malay.Keywords: Papuan Malay, Serial verb constructions, dependent serialization, co-dependent serialization, monoclausality